Circular zymogens of human ribonuclease 1 - Windsor, Ian W. (Protein Sci, 2019)
The endogenous production of enzymes as zymogens provides a means to control catalytic activities. Here, we describe the heterologous production of ribonuclease 1 (RNase 1), which is the most prevalent secretory ribonuclease in humans, as a zymogen. In folded RNase 1, the N and C termini flank the enzymic active site. By using intein‐mediated cis‐splicing, we created circular proteins in which access to the active site of RNase 1 is obstructed by an amino‐acid sequence that is recognized by the HIV‐1 protease. Installing a sequence that does not perturb the RNase 1 fold led to only modest inactivation. In contrast, the ancillary truncation of residues from each terminus led to a substantial decrease in the catalytic activity of the zymogen with the maintenance of thermostability. For optimized zymogens, activation by HIV‐1 protease led to a > 10(4)‐fold increase in ribonucleolytic activity at a rate comparable to that for the cleavage of endogenous viral substrates. Molecular modeling indicated that these zymogens are inactivated by conformational distortion in addition to substrate occlusion. Because protease levels are elevated in many disease states and ribonucleolytic activity can be cytotoxic, RNase 1 zymogens have potential as generalizable prodrugs.